Adoptive Gay Father Families: A Longitudinal Study of Children's Adjustment at Early Adolescence. Issue 1 (3rd September 2020) - McConnachie, Anja L.; Ayed, Nadia; Foley, Sarah; Lamb, Michael E.; Jadva, Vasanti; Tasker, Fiona; Golombok, Susan
Abstract : Findings are presented from the second phase of a UK longitudinal study of 33 gay father, 35 lesbian mother, and 43 heterosexual parent families when their adopted children reached early adolescence. Participants predominantly lived in urban/suburban areas and were mostly white and well‐educated. Standardized interviews, observations, and questionnaires of parental mental health, parent–child relationships, and adolescent adjustment were administered to parents, children, and teachers between 2016 and 2018. There were few differences between family types. However, adjustment problems had increased in all family types, with better parenting quality and parental mental health associated with fewer adjustment problems. The findings contribute to adoption policy and practice, and to theoretical understanding of the role of parental gender in child development.